Neighbor Session Solutions for Integrated Routing Protocols - Martin Kontsek; Pavel Segec; Marek Moravcik; Juraj Smiesko (Applied Sciences)
This paper proposes a novel methodology for the design of dual-stack IP routing protocols focused on neighborships and routing messages transport. The first part describes currently used dual-stack IP routing protocols, their history, and key features. The description of four identified combinations based on a number of neighbor sessions and protocol used for the transport of routing messages is presented afterward. These combinations are introduced as Protocol Integration Solution Classes (PISCs) in this paper. Colored Petri nets (CPNs) are selected as a formal method to create a model of each PISC. The following parts deal with a detailed description and analysis of the created Protocol Integration Solution Class models, which are also verified and compared with each other. Based on the comparison of each PISC model simulation step, the PISC 2 class is selected as the most efficient one. The last part of the paper formulates recommendations for the dual-stack IP routing protocol design based on the results presented in this paper.